Financial Sector Reforms and Exchange Arrangements in Eastern Europe - Calvo, Guillermo (Occasional Papers; Occasional Paper ;, 1993)
The two papers draw from the brief yet radical reform experiences of five countries-Bulgaria, former Czechoslovakia, Hungary, Poland, and Romania. The first paper describes the financial sector reforms untertaken by these countries since the 1980s, as well as the problems encountered. It also discusses the roles privatization, stabilization policies, and prudential supervision can play in the financial sector development of these countries. The second paper analyzes the different exchange arrangements as they apply to previously centrally planned economies; examines the general arguments for convertability in these countries; and considers the desirable degree of exchange rate flexibility.